Towards an integrated model for child and family services in central Australia: An innovative model for the delivery of child and family services - Chee, D.; Boffa, John; Tilton, E. (Australasian Medical Publishing, 2016)
The Central Australian Aboriginal Congress is a large Aboriginal community-controlled health service based in Alice Springs in the Northern Territory. Since the 1970s, Congress has developed a comprehensive model of primary health care delivering evidence-based services on a foundation of cultural appropriateness. In recent years, the community-elected Congress Board has focused on improving the developmental outcomes of Aboriginal children. This has led to the development of an innovative model for the delivery of child and family services, based on the belief that the best way to “close the gap” is to make sure it is not created in the first place.